Instructions in package inserts intended for the use of medicines for dyspepsia and constipation during lactation - Danillo Alencar Roseno; Tatiana da Silva Sempé; Thanyse de Oliveira Schmalfuss; Camila Giugliani; Tatiane da Silva Dal Pizzol (Sociedade Brasileira de Medicina de Família e Comunidade, 2024)
Introduction: The safety and effectiveness of medication use during lactation are concerns for mothers and healthcare professionals. This research analyzes the instructions on the leaflets of medications commonly prescribed for dyspepsia and constipation, which aims to provide essential information to guide therapeutic decisions during this crucial period of motherhood. Objectives: To analyze the information in package inserts about contraindications of drugs for dyspepsia and constipation during breastfeeding, verifying whether these are consistent with scientific evidence. Methods: Drugs for dyspepsia and constipation were selected according to the Anatomical Therapeutic Chemical (ATC) classification and active registry in Brazil. The presence of contraindications for the use of medications in the health professional's and patient's package inserts was compared with the information in the technical manual of the Ministry of Health, Medications and Mothers' Milk, LactMed, UptoDate, Micromedex, Documento Científico da Sociedade Brasileira de Pediatria and Reprotox. Results: No information about use during breastfeeding was found in 20.0 and 24.3% of leaflets for dyspepsia and constipation, respectively. The agreement between the leaflets of medications for dyspepsia and the sources consulted was low (27.2% of the leaflets contraindicated the medication during lactation, while in the sources the percentage of contraindication varied from 0 to 8.3%). In relation to medicines for constipation, 26.3% of the leaflets contraindicated them, while in the sources the percentage ranged from 0 to 4.8%. Conclusions: The study pointed out that at least two out of every ten package inserts for dyspepsia and constipation do not provide adequate information on the use of these drugs in infants, and also shows low concordance between the text of the package inserts and the reference sources regarding compatibility of the drug with breastfeeding.